(untitled) (The Batuk, 2025)
It is widely agreed that all children must be given equal opportunity of education. The ground reality, however, falls far short of this ideal, namely that children do not have the same or comparable opportunity of education. In this context, the objective of this study is to investigate to what extent educational opportunity is determined by type of school. This study discusses how neo liberal economic policies has differentiate the educational opportunity among the students of public and institutional schools in Nepal. The survey questionnaire developed through Delphi was used to collect data from 292 students of 8 schools (community and institutional). An independent t-test followed by G power analysis shows a significant difference of educational opportunity across student’s school types. Children from community schools do not enjoy the same educational opportunity as those in institutional schools. So, the major implication of this study is that the equitable distribution of resource generally is fundamental to ensure the equal educational opportunity of all children, studying in community and institutional schools alike.